On a collection of calappid crabs (Crustacea: Decapoda: Brachyura) from Fiji, with a description of a new species of Mursia - Galil, Bella S. (Zootaxa, 2013)
Seven species of calappid crabs were identified from material collected during four IRD-MNHN expeditions conducted in 1998 and 1999 in shallow and deep waters off Fiji. Six species are reported for the first time from the islands. One new species, Mursia murimura n. sp., is described and illustrated. The new species differs from the closely related M. diwata Galil & Takeda, 2004, with which it shares a stout, distally auriculated first male pleopod, by possessing much longer lateral carapacial and cheliped spines.